2017
DOI: 10.1093/ecco-jcc/jjx150
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Outcomes Over Time With Exclusive Enteral Nutrition Compared With Steroids in Children With Mild to Moderate Crohn’s Disease: Results From theGROWTH CDStudy

Abstract: Use of EEN was associated with higher remission rates and a trend toward better growth but with similar relapse and complication rates in new-onset mild to moderate paediatric CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 19 publications
(27 reference statements)
1
56
2
7
Order By: Relevance
“…Other key endpoints including factors determining risk for complications (fibrostenosing disease, penetrating disease and perianal complications), a model for highrisk disease, and the effect of initial treatment on outcomes, form the basis of separate studies of the GROWTH CD cohort, several of which are ongoing or already published and thus are not included. 12,19,20 Patients' characteristics at baseline and 12 weeks after treatment initiation were compared between those who had relapse and those who didn't. Categorical variables were compared using Chi-square test or Fisher's exact test and continuous variables using independent samples ttest or Mann-Whitney test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other key endpoints including factors determining risk for complications (fibrostenosing disease, penetrating disease and perianal complications), a model for highrisk disease, and the effect of initial treatment on outcomes, form the basis of separate studies of the GROWTH CD cohort, several of which are ongoing or already published and thus are not included. 12,19,20 Patients' characteristics at baseline and 12 weeks after treatment initiation were compared between those who had relapse and those who didn't. Categorical variables were compared using Chi-square test or Fisher's exact test and continuous variables using independent samples ttest or Mann-Whitney test.…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoint of this aspect of the GROWTH CD study was to determine a model for early relapse (by week 78), based on variables from weeks 0 and 12. Other key endpoints including factors determining risk for complications (fibrostenosing disease, penetrating disease and perianal complications), a model for highrisk disease, and the effect of initial treatment on outcomes, form the basis of separate studies of the GROWTH CD cohort, several of which are ongoing or already published and thus are not included …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohen-Dolev et al demonstrated that EEN was superior to corticosteroids for induction of remission and linear growth in a multicentre prospective inception cohort of mild-to-moderate CD at diagnosis. EEN was not superior with respect to other outcomes such as time to relapse or complications over 2 years 72. Grover et al performed a prospective trial to assess mucosal healing by performing colonoscopy before and after 8 weeks of EEN with azathioprine.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, several systematic reviews have suggested that there is evidence, albeit weak, that EEN is less effective than conventional treatment with corticosteroids . However, the results from individual studies in children are more supportive of EEN . For example, the results from the GROWTH‐CD study demonstrated that EEN was more effective at inducing remission than corticosteroids and also offered greater benefits in terms of improved growth .…”
Section: Introductionmentioning
confidence: 99%